Vulnerability to COVID-19: cluster analysis of census tracts in Malaga, Spain - García-Peña, María del Carmen; Molina-Luque, Julián; Cabrera-Yeto, Susana; Ruiz-Sinoga, José Damián (Taylor&Francis, 2023)
The United Nations 2030 Agenda recognized the importance of focusing on cities to achieve sustainable development goals. The COVID 19 pandemic reaffirmed the need to consider spatial variables when analyzing the impact of a risk or an epidemic. Many studies have assessed the impact of this pandemic on countries and its connection with numerous population-related factors, such as vulnerability and resilience. However, there have been less spatial analyses at an urban scale also considering time as a variable. In spite that, some researchers have recently shown how the patterns of the pandemic evolution is changing in time. We performed a case study in Malaga (Spain) using a tempo-spatial analysis with the purpose of going as deep as possible into the micro-scale of the pandemic impacts, without leaving anyone behind. The micro-level research using composite indexes and cluster analysis clarify the living conditions of people. The results show some patterns a of the spatial segregation in the neighborhoods that could oriented better integrated policies and good governance in the recovery process.
Keywords: Personas desfavorecidas; Pandemia de la Covid-19, 2020- - Aspectos económicos - Málaga; COVID-19; 2030 Agenda; Vulnerability; Spatial segregation; Clusters